2012
DOI: 10.1002/nau.22360
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of stretch‐induced Rho‐kinase activation in the generation of bladder tone

Abstract: This study demonstrates that the ROK pathway is constitutively active and stretch further activates the ROK pathway, which contributes to the generation of bladder tone, thereby affecting bladder compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…This pilot study identified the biomechanical bladder property of dynamic elasticity during a specially designed repeat fill‐and‐empty UD protocol in patients with OAB. Dynamic elasticity is the UD correlate of reversible strain softening (adjustable preload tension) previously identified in isolated human, rabbit, and mouse DSM tissue strips . Using our UD protocol, we were able to generate a novel metric for detrusor muscle function during the filling phase of micturition.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This pilot study identified the biomechanical bladder property of dynamic elasticity during a specially designed repeat fill‐and‐empty UD protocol in patients with OAB. Dynamic elasticity is the UD correlate of reversible strain softening (adjustable preload tension) previously identified in isolated human, rabbit, and mouse DSM tissue strips . Using our UD protocol, we were able to generate a novel metric for detrusor muscle function during the filling phase of micturition.…”
Section: Discussionmentioning
confidence: 95%
“…In pre‐clinical studies, adjustable preload tension, the pre‐clinical correlate of dynamic elasticity, has been attributed to cycling actomyosin crossbridges . Furthermore, adjustable preload tension has been shown to be under the influence of the rho‐kinase pathway in multiple species, including humans, and may offer a target for future intervention in these types of voiding dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro models of mechanical stretch, where BSM cells are cultured on a deformable membrane, has been used to demonstrate that the phosphatase, and contributes to agonist-induced Ca 2ϩ sensitization in smooth muscle contraction (43,44). The ROCK pathway is constitutively active, and stretch enhances ROCK pathway activation, contributing to myogenic tone generation in bladder wall smooth muscle, thereby affecting bladder compliance (41). Inhibiting ROCK with the inhibitor Y-27632 induced concentration-dependent relaxation of detrusor muscle strips at resting tension (41).…”
Section: Discussionmentioning
confidence: 99%
“…The ROCK pathway is constitutively active, and stretch enhances ROCK pathway activation, contributing to myogenic tone generation in bladder wall smooth muscle, thereby affecting bladder compliance (41). Inhibiting ROCK with the inhibitor Y-27632 induced concentration-dependent relaxation of detrusor muscle strips at resting tension (41). Furthermore, spontaneously tonic smooth muscle, such as internal anal sphincter, has higher levels of RhoA/ROCK activity compared with phasic smooth muscle, indicating a role for ROCK in the maintenance of basal tone (35).…”
Section: Discussionmentioning
confidence: 99%